Flow and Coral Morphology Control Coral Surface pH: Implications for the Effects of Ocean Acidification - Chan, Neil C. S.; Wangpraseurt, Daniel; Kühl, Michael; Connolly, Sean R. (Frontiers in Marine Science, 2016)
The future impact of ocean acidification (OA) on corals is disputed in part because mathematical models used to predict these impacts do not seem to capture, or offer a framework to adequately explain, the substantial variability in acidification effects observed in empirical studies. The build-up of a diffusive boundary layer (DBL), wherein solute transport is controlled by diffusion, can lead to pronounced differences between the bulk seawater pH, and the actual pH experienced by the organism, a factor rarely considered in mathematical modelling of ocean acidification effects on corals. In the present study, we developed a simple diffusion-reaction-uptake model that was experimentally parameterized based on direct microsensor measurements of coral tissue pH and O2 within the DBL of a branching and a massive coral. The model accurately predicts tissue surface pH for different coral morphologies and under different flow velocities as a function of ambient pH. We show that, for all cases, tissue surface pH is elevated at lower flows, and thus thicker DBLs. The relative effects of OA on coral surface pH was controlled by flow and we show that under low flow velocities tissue surface pH under OA conditions (pHSWS = 7.8) can be equal to the pH under normal conditions (pHSWS = 8.2). We conclude that OA effects on corals in nature will be complex as the degree to which they are controlled by flow appears to be species specific.